Phytoplankton Community of Taylor Creek in the Niger Delta Using Diversity Indices - Nwabueze Ogamba Emmanuel; Edure Charles Embelemi; Chibueze Izah Sylvester (Journal of Plant and Animal Ecology, 2019)
This study evaluated the phytoplankton community of Taylor creek from Polaku to Agbia between November 2013 and July 2014. Sampling was carried out in 12 locations along the stretch of the creek following standard protocol. The phytoplankton enumeration was done and identified accordingly. In all the 12 locations, 100 species of phytoplankton belonging to 14 taxonomic groups including Bacillariophyta (31 species), Chlorophyta (25 species), Pyrrophyta (4 species), Cyanophyta (17 species), Spermatophyta (9 species), Euglenophyta (3 species), Phaeophyta (1 species), Heterokontophyta (2 species), Myxophyta (1 species), Xanthophyta (1 species), Chrysophyta (2 species), Lycopodiophyta (1 species), Cryptophyta (1 species), Dinophyta (2 species). Bacillariophyta, Chlorophyta, Cyanophyta and Spermatophyta with occurrence rate of 36%, 34%, 10% and 10%, respectively were the predominant phytoplankton in the study area occurring in all the locations across the period of the study. The various species have some distinct environmental condition that enable them thrive in their niche, and this determines the structure of the phytoplankton in the study area. The diversity indices provided information about the distribution and health condition of the creek. The study showed significant relationships between Shannon-Wiener, Menhinick, Margalef, equitability and Fisher-alpha indices. The ecosystem showed moderate to heavy pollution based on Shannon Wiener index. There is the need for improved method of waste disposal and other anthropogenic activities being carried in and/ or within the creek.